Characterization of stress‐responsive lncRNAs in Arabidopsis thaliana by integrating expression, epigenetic and structural features. (21st October 2014) - Di, Chao; Yuan, Jiapei; Wu, Yue; Li, Jingrui; Lin, Huixin; Hu, Long; Zhang, Ting; Qi, Yijun; Gerstein, Mark B.; Guo, Yan; Lu, Zhi John
Summary Recently, in addition to poly(A)+ long non‐coding RNAs (lncRNAs), many lncRNAs without poly(A) tails, have been characterized in mammals. However, the non‐polyA lncRNAs and their conserved motifs, especially those associated with environmental stresses, have not been fully investigated in plant genomes. We performed poly(A)− RNA‐seq for seedlings of Arabidopsis thaliana under four stress conditions, and predicted lncRNA transcripts. We classified the lncRNAs into three confidence levels according to their expression patterns, epigenetic signatures and RNA secondary structures. Then, we further classified the lncRNAs to poly(A)+ and poly(A)− transcripts. Compared with poly(A)+ lncRNAs and coding genes, we found that poly(A)− lncRNAs tend to have shorter transcripts and lower expression levels, and they show significant expression specificity in response to stresses. In addition, their differential expression is significantly enriched in drought condition and depleted in heat condition. Overall, we identified 245 poly(A)+ and 58 poly(A)− lncRNAs that are differentially expressed under various stress stimuli. The differential expression was validated by qRT‐PCR, and the signaling pathways involved were supported by specific binding of transcription factors (TFs), phytochrome‐interacting factor 4 (PIF4) and PIF5. Moreover, we found many conserved sequence and structural motifs of lncRNAs from different functional groups (e.g. a UUC motif responding to salt and a AU‐rich stem‐loop responding to cold), indicated that the conserved elements might be responsible for the stress‐responsive functions of lncRNAs.